Influence of collection method and collection time on survival, sexual proportion and number of spittlebug adults captured - Nilakhe, Shashank S.; Hewitt, George B.; Paschoal, Gustavo O.; Buainain, Conceição M.; Souza, Antonia R. Roel (Pesquisa Agropecuaria Brasileira, 2014)
Adults of Zulia entreriana (Berg.) and Deois flavopicta (Stal) collected in ten sweep samples of a sweep-net and transferred to cages using an aspirator tended to live shorter than those transferred using a container lined with cotton. Sweeping itself did not affect the adult survival. Adults collected in 10, 30 or 50 sweep samples lived the same period as those captured by pulling an open end of a cage 20 cm above the pasture at 30º angle. Spittlebugs collected at 8 a.m. - 9 a.m. lived longer than those collected at midday - 1 p.m. or 5 p.m. - 6 p.m. More adults were captured by sweeping at 5 p.m. - 6 p.m. than at 8 a.m. - 9 a.m. or midday - 1 p.m. A comparison of sexual proportions of adult captured by sweeping with those based on all the adults in 1 m2 pasture areas showed that the sweep-net method tended to underestimate the proportion of females.